PERSEPSI PENGGUNA TERHADAP KETERSEDIAAN DAN KUALITAS KOLEKSI BUKU TEKS DI PERPUSTAKAAN SEKOLAH MENENGAH KEJURUAN NEGERI 1 KUTA SELATAN - Nurul Farida (D3 Perpustakaan FISIP UNUD, 2025)
This research aims to describe the user perception, specifically of students at State Vocational High School 1 (SMK Negeri 1) Kuta Selatan, regarding the availability and quality of the textbook collection in the school library. The research utilizes a quantitative descriptive method with a survey approach, where primary data was collected through a Likert scale questionnaire from 45 respondents. Data analysis resulted in findings that the overall user perception of the collection falls into the Good category (Availability 3.92; Quality 4.09). For the Collection Availability variable, the library's main strength lies in the Accessibility dimension (4.37), which achieved the Very Good category, indicating effective arrangement and signage. However, the total score for this variable is held back by the Quantity and Title Completeness dimension (3.71), which suggests room for improvement in the aspect of the number of mandatory textbook copies. Meanwhile, the Collection Quality variable was consistently rated Good, supported by high scores in Physical Condition (4.18) and Content Currency (4.00). The conclusion of the study indicates that the library has excelled in the physical and substantive aspects of its collection, but needs to focus improvement efforts on increasing the stock of textbooks to optimize user satisfaction.